2004
DOI: 10.1080/19485565.2004.9989088
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between socioeconomic status and infant mortality in metropolitan Ohio, 1999–2001*

Abstract: Empirical evidence has consistently documented the direct relationship between infant mortality and socioeconomic inequality in the United States and numerous other countries. While the majority of these studies reveal an inverse relationship between socioeconomic level and infant mortality, not even this finding is free from disagreement. Furthermore, the specific nature and magnitude of this relationship has varied over time.This study will examine the relationship between socioeconomic status and infant mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…This relationship is well-established in the literature, and several studies had reported similar results. As examples, Goza et al showed higher IMR among populations with lower economic status, [20] and Hales et al reported higher IMRs in countries with lower gross domestic product (GDP) per capita and societies with higher inequalities in income distribution [21]. Moreover, we showed a relatively high coefficient for wealth index in our model of NMR, which possibly stems from social factors like greater family stability, better living conditions, fewer children, and lower levels of environmental exposure among wealthier families, as well as the relationship between the role of specialized care and facilities in improving neonatal mortality in rural areas, and availability of these services to people with higher average wealth status.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is well-established in the literature, and several studies had reported similar results. As examples, Goza et al showed higher IMR among populations with lower economic status, [20] and Hales et al reported higher IMRs in countries with lower gross domestic product (GDP) per capita and societies with higher inequalities in income distribution [21]. Moreover, we showed a relatively high coefficient for wealth index in our model of NMR, which possibly stems from social factors like greater family stability, better living conditions, fewer children, and lower levels of environmental exposure among wealthier families, as well as the relationship between the role of specialized care and facilities in improving neonatal mortality in rural areas, and availability of these services to people with higher average wealth status.…”
Section: Discussionmentioning
confidence: 99%
“…The use of infant death, instead of incidence, to infer the causal relationship between solvent exposure and birth defects was limited to available data and not perfect. Because infant mortality can reflect socioeconomic status (Goza et al, 2004; Hertel‐Fernandez, 2007), parental education has been controlled by using regression modeling. Besides, these workers employed in an international company had higher wages or socioeconomic status than those from other traditional manufacturers in Taiwan (RCA, 1973, 1977; Taiwan Bureau of Health Promotion, 2003; Taiwan Directorate General of Budget and Accounting and Statistics, 1978–1988).…”
Section: Discussionmentioning
confidence: 99%
“…Kabupaten kota yang mampu meningkatkan PDRB perkapita sebesar satu jutaan rupiah, maka akan menurunkan AKB sebesar 0,00009 per 1000 kelahiran hidup, dengan asumsi variabel bebas lainnya dianggap konstan. Hasil dari penelitian ini sejalan dengan beberapa penelitian sebelumnya, yaitu Warsita dan Marhaeni (2015), Danawi dan Ogbonna (2014), Hulya dan Arik ( 2009), Nishiyama (2011), Goza et al (2004), Rodgers (2002), Dallolio et al (2012), Kurniawati (2015), Barbus (2011), Flegg (1982, , dan Sadetskaya (2015). Beberapa peneliti tersebut berpendapat bahwa PDRB perkapita yang lebih tinggi merupakan prasyarat untuk mendapatkan lingkungan dan makanan yang lebih sehat, serta pelayanan kesehatan yang lebih baik.…”
Section: Analisis Dan Pembahasan Angka Kematian Bayi DI Jawa Timurunclassified